Numerical Investigation of Effects of G-Jitter on Buoyant Laminar Diffusion Flame - Mondal S.S.; Kumar N.; Ghosh P. (My University, 2025)
Numerical prediction of a confined, co-flowing, laminar jet diffusion flame has been investigated under sinusoidal "g-jitter"to describe the flame structure; this type of flame-body force interaction is typical of a microgravity environment such as in the spacecraft. We introduced g-jitter in the direction orthogonal to the fuel and air inflow. We show that the lower frequencies (0.1-0.5 Hz) of sinusoidal g-jitter significantly affected the flame geometry and behavior. The majority of the flame structure was found to oscillate directly in response to the imposed g-jitter. It has also been observed that nonlinearity in the response behaviors is more prominent in the reaction zone of the flame. © 2021 SAE International.